Iron-mediated remediation of arsenic-induced suppression of root morphogenesis and radial oxygen loss in wetland plant - Jiang, Sitong; Zhu, Zhengyu; Pan, Yitong; Shi, Rongrong; Wang, Zhixi; Uddin, Mohammad Mazbah; Wang, Song; Liu, Jingchun; Mei, Kang (Frontiers in Plant Science, 2025)
Arsenic (As) contamination in paddy soils disrupts root morphogenesis and radial oxygen loss (ROL), yet the dynamic interplay between iron (Fe) plaque formation and plant physiological adaptation remains poorly understood across temporal scales. This study investigated Fe-mediated mitigation of inorganic As toxicity through hydroponic experiments with varying As (0, 10, and 30 μmol/L) and Fe (0–100 μmol/L) concentrations over exposure periods ranging from acute to chronic scenarios. Pot experiments revealed that 1-week high-As (HAs) exposure reduced chlorophyll content by 28% and suppressed ROL by 50% compared with the control group (CK), whereas prolonged low-As (LAs) exposure induced partial chlorophyll recovery (LAs > CK > HAs). Fe supplementation enhanced root biomass by 1.18–2.39 times under chronic As stress and significantly increased ROL rates by 1.38–2.83 times through Fe-plaque formation, which sequestered 38%–52% of root-associated As. Root porosity peaked at 9.84% under As–Fe co-treatment but showed an inverse correlation with ROL. Anatomical analysis revealed Fe-driven restoration of aerenchyma (46.32% cross-sectional area) and reinforcement of lignification barriers. These findings highlight Fe’s dual role in alleviating As toxicity through physical immobilization and physiological adaptation, offering insights into Fe-based remediation strategies for As-contaminated wetlands.